Hepatic protective effects of sulforaphane through the modulation of inflammatory pathways. Issue 4 (2nd April 2020) - Lee, Changhun; Yang, Sumin; Lee, Bong-Seon; Jeong, So Yeon; Kim, Kyung-Min; Ku, Sae-Kwang; Bae, Jong-Sup
Abstract: The aim of this study was to investigate the effects of sulforaphane (SFN) on lipopolysaccharide (LPS)-induced liver failure, and to elucidate underlying mechanisms. SFN, a natural isothiocyanate present in cruciferous vegetables such as broccoli and cabbage, is effective in preventing carcinogenesis, diabetes, and inflammatory responses. Mice were treated intravenously with SFN at 12 h after LPS treatment. LPS significantly increased mortality, serum levels of liver damage markers, and inflammatory cytokines, and toll-like receptor 4 (TLR4) protein expression, which were reduced by SFN. Our results suggest that SFN protects against LPS-induced liver damage, indicating its potential to treat liver diseases. Graphical Abstract: